Retention and Attrition in Academia: A Time-to-event Analysis - Muhwezi, Keneth; Wamala, Robert; Atuhaire, Leonard K. (Kenya Studies, 2013)
An abundance of literature exists regarding retention and attrition of teachers in primary and secondary education levels. This however is not the case with regards to academic staff in universities. Administrative records of 1,486 academic staff recruited at Makerere University in the period 1987–2012 provide a basis for making an assessment of this issue. Duration of university service was modeled in the analysis by characteristics of academic staff (age, gender, and marital status), discipline area, academic qualifications and rank using a Cox regression. In the results, a median duration of service among staff who left the University by December 2012 (4.56 years, range 0.22-23.32) confirms arguments of low retention of academia. Low retention in university service was more likely among young academic staff, those at lower academic ranks and staff with high academic qualifications at the time of recruitment. The findings demonstrate similarities in retention and attrition of teachers in primary, secondary and university levels.
Keywords: Employee Retention and attrition; Academic Staff; Makerere University